INTERJECTION HE SOAYA LE...! IN NIASNESE: A NATURAL SEMANTIC METAFUNCTION APPROACH - VIVI NOVALIA SITINJAK; NENCY ANGELITA GEA; TRISMAN NDURU; WIDYA CHRISTINA HUTASOIT; YANTHY PURBA (LINGUISTICA, 2023)
This study explores the interjection of He Soaya le…! in Nias language using a descriptive qualitative method. Words that denote reactions or spontaneous expressions are interjections. The Nias language has an interjection that is similar to the exclamation of oh my God, namely He Soaya le...! Where this interjection is one of the quite iconic interjections in the daily conversation of the Nias people.  This research aims to know the meaning of the Interjection He Soaya le...! . In this paper, researchers identify Nias interjections in the Nias language using the Natural Semantic Metafunction approach. The method used in this study is a qualitative research method, namely research that uses written and oral data sources. The data is taken from a dialogue in the comedy-drama series entitled Abunawa. Distribution and contextual methods are the methods used in this study to obtain data. From the results obtained in this study, there is one meaning of the interjection He Soaya le...! Namely shock, fear and panic, and emotional expressions that can be formed through physiological changes in humans. In Nias language, it is also expressed in two semantic aspects of its metafunction, namely emotive and cognitive aspects. From the results of this research, it is hoped that it can become a source of knowledge and understanding for other people of different ethnicities from the people of Nias and can avoid misunderstandings about a language.